Custo e qualidade de fabricação de um flange em aço carbono via manufatura aditiva por deposição a arco - Ferraresi, Henrique Nardon (2023)
Additive Manufacturing (AM) by Directed Energy Deposition (DED) is among the most mature technologies commercially available for manufacturing functional metal components. The GMA-DED process, that uses the welding sources, offers high deposition rates, low equipment and input costs, and a wide range of materials compared to powder-based AM processes. For these reasons, the application of GMA-DED has expanded to the oil and gas (O&G) sector, standing out as a technology capable of providing greater flexibility and agility in replenishing inventories, especially for low-movement, medium-complexity, and large components. In the same direction, several regulatory bodies associated with the industry have established rigorous standards to ensure the integrity of these components in service. However, the relationship between time, cost, quality, and certification of these components is still largely unknown. The objective is to analyze the costs and quality in the manufacturing of neck flanges using GMA-DED additive manufacturing in an on-demand parts replacement scenario. The research was conducted with a focus on real-case application, and therefore, the maximum effort was made to meet the requirements for GMA-DED flange certification. To achieve this, the three main standards for this case were analyzed: AWS D20.1, ASME B16.5, and ASTM 182. Based on the regulatory requirements, an initial manufacturing methodology was developed to evaluate the activities involved, manufacturing time, resources used, chemical and mechanical properties of the material, process robustness, and, most importantly, to confirm the actual feasibility of applying the component. The methodology was developed based on the deposition of three neck flanges using ER90S-B3 wire, varying between two GMA-DED processes, two deposition equipment, with and without thermal management, three deposition paths, and with and without heat treatment. Finally, based on the methodology, production costs were determined using full costing, the selling price was estimated using a markup, and a comparison was made with the selling price of a conventional flange. It was concluded that the GMA-DED deposited flange has sufficient quality for use in service. The estimated price for GMA-DED manufacturing was found to be 5 to 10 times more expensive than conventional methods. However, depending on the scenario, the replacement of this component can be dozens of times faster.